Light through a prism : social justice teaching for refugee and displaced students - Rodriguez, Terri, 1967-; Ghassa-Khalil, Odeese; Meagher, Jennifer; Omar, Ayan Amoud; Ergen, Lauren; Mahalingappa, Laura, 1975- (Rowman & Littlefield, 2024)
Light Through a Prism explores stories of K-12 educators committed to social justice pedagogy, especially with refugee and displaced students, as they navigate the complexities of pandemic-era schooling.